The desire of autonomy: A lever for vaccination of the elderly? Results of a qualitative study - Alexandra Addario; Mathilde Pardo; Gaëtan Gavazzi; Bienvenu Bongue; Thomas Célarier; Solène Dorier; Nathalie Barth; Elisabeth Botelho-Nevers (Taylor & Francis Group, 2024)
The COVID-19 pandemic has highlighted the challenges of vaccination and the infectious risks among the elderlies. However, immunization rates for recommended vaccines in this population are insufficient in France. We aimed in this study to identify the levers and obstacles to vaccination among seniors, and to establish the arguments that could lead to some new vaccination behaviors. A qualitative survey based on 14 semi-structured interviews was conducted with people aged 65 and over, living at home in the Auvergne Rhône-Alpes region (France) from March to May 2022. The interviews were recorded, entirely transcribed, then subjected to a thematic content analysis. The results show that participants are keen to preserve their health by maintaining their physical capacity, taking regular exercise and eating a balanced diet. However, vaccination was not mentioned as a mean of preventing infectious diseases. Infections were not perceived as a cause for concern. Furthermore, the physical and cognitive consequences of infectious diseases, which could result in a loss of autonomy, were not known. These elements could be a good lever to bring hesitant elderly people to reconsider their position toward vaccination. Vaccines were not seen as a strategy to prevent loss of autonomy among elderlies. Since vaccines against influenza, COVID-19, shingles, pneumococcus have proved to be effective in protecting against cardiovascular events, this argument might be the starting point for a prevention campaign for the elderly.